Application of endocrine disruptor screening program fish short‐term reproduction assay: Reproduction and endocrine function in fathead minnow (Pimephales promelas) and killifish (Fundulus heteroclitus) exposed to Bermuda pond sediment. (9th April 2015) - Fort, Douglas J.; Mathis, Michael; Fort, Chelsea E.; Fort, Hayley M.; Bacon, Jamie P.
Abstract A modified tier 1 Endocrine Disruptor Screening Program (EDSP) 21‐d fish short‐term reproduction assay (FSTRA) was used to evaluate the effects of sediment exposure from freshwater and brackish ponds in Bermuda on reproductive fecundity and endocrine function in fathead minnow (Pimephales promelas) and killifish (Fundulus heteroclitus). Reproductively active male and female fish were exposed to control sediment and sediment from 2 freshwater ponds (fathead minnow) and 2 marine ponds (killifish) contaminated with polyaromatic hydrocarbons and metals via flow‐through exposure for 21 d. Reproductive fecundity was monitored daily. At termination, the status of the reproductive endocrine system was assessed by the gonadosomatic index, gonadal histology, plasma steroids (estrogen [E2], testosterone [T], and 11‐ketotestosterone [11‐KT]), steroidogenic enzymes (aromatase and combined 3β/17β ‐hydroxysteroid dehydrogenase [3β/17β‐HSD]), and plasma vitellogenin (VTG). Decreased reproductive fecundity, lower male body weight, and altered endocrinological measures of reproductive status were observed in both species. Higher plasma T levels in female minnows and 11‐KT levels in both male and female minnows and female killifish exposed to freshwater and brackish sediments, respectively. Decreased female E2 and VTG levels and gonadal cytochrome P19 (aromatase) activity were also found in sediment exposed females from both species. No effect on female 3β/17β‐HSD activity was found in either species. The FSTRA provided a robust model capable of modification to evaluate reproductive effects of sediment exposure in fish. Environ Toxicol Chem 2015;34:1283–1295. © 2015 SETAC